Training on Effective and Efficient Mosque Financial Governance at Masjid Mujahadah Pekanbaru - Wali Saputra (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2025)
This community engagement program was designed to strengthen the capacity of mosque administrators in managing mosque finances effectively, efficiently, transparently, and accountably. Implemented at Masjid Mujahadah in Pekanbaru, the program adopted an educational and participatory approach that integrated interactive lectures, hands-on technical workshops, and direct mentoring sessions for mosque administrators. The training materials covered the fundamental concepts of Good Financial Governance (GFG), standardized financial recording systems, and the use of simple digital tools to enhance transparency and accuracy in financial reporting. The outcomes revealed a notable improvement in participants’ financial literacy, particularly in preparing financial reports, managing budgets, and implementing transparent administrative procedures. Moreover, the program fostered sustainable impacts by promoting technology-driven financial governance, strengthening congregational trust, and establishing a collaborative framework among academics, the community, and mosque administrators to advance professional and integrity-based mosque financial management.